Inter-assay diagnostic accuracy of cerebrospinal fluid kappa free light chains for the diagnosis of multiple sclerosis - Dekeyser, Cathérine; De Kesel, Pieter; Cambron, Melissa; Vanopdenbosch, Ludo; Van Hijfte, Liesbeth; Vercammen, Martine; Laureys, Guy (Frontiers in Immunology, 2024)
Results: 263 participants were included (MS n=80). Optimal diagnostic cut-off values for the κFLC index (Freelite®-Optilite: 7.7; N Latex®-BNII: 4.71), κIgG index (Freelite®-Optilite: 14.15, N Latex®-BNII: 12.19) and CSF κFLC/IgG ratio (Freelite®-Optilite: 2.27; N Latex®-BNII: 1.44) differed between the two methods. Sensitivities related to optimal cut-off values were 89.9% (Freelite®-Optilite) versus 94.6% (N Latex®-BNII) for the κFLC index, 91% (Freelite®-Optilite) versus 92.2% (N Latex®-BNII) for the κIgG index and 81.3% (Freelite®-Optilite) versus 91.4% (N Latex®-BNII) for the CSF κFLC/IgG ratio. However, for iCSF-κFLC, optimal diagnostic cut-off values (0.36 mg/L) and related specificities (81.8%) were identical with related diagnostic sensitivity of 89.9% for Freelite®-Optilite and 90.5% for N Latex®-BNII. The diagnostic performance of the κFLC index (area under the curve (AUC) Freelite®-Optilite:0.924; N Latex®-BNII: 0.962) and κIgG index (AUC Freelite®-Optilite:0.929; N Latex®-BNII: 0.961) was superior compared to CSF oligoclonal bands (AUC 0.898, sensitivity 83.8%, specificity 95.9%).